The Use of Gallery Walk in Teaching Descriptive Text to Promote Higher Order Thinking Skills for 7th Graders - Khasanah, Uswatun; Purwati, Oikurema; Munir, Ahmad (Department of English Language Education, UIN Sunan Ampel Surabaya, 2019)
The purpose of this research was to analyze the use of Gallery Walk in teaching reading descriptive text and how it promoted higher order thinking skills for 7th graders. The subject of the research was the teacher of Junior High School in Surabaya. In finding the sample of the research, the participant was the 7th grade students of Junior High School. The data of the research was the teacher and to gain the detail data and information, the researcher gathered the data by using two techniques, they were observation and documentation in four meetings in the classroom. The teacher used Gallery Walk method in teaching descriptive text and to promote the students’ higher order thinking skills the teacher implemented the step of the lesson plan, such as Grouping, distributing material, students’ presentation, sharing knowledge, collective reflection and conclusion. The result of the data showed that the use of Gallery Walk in teaching reading descriptive text can promote higher order thinking skills of 7th graders, especially in level C3 to C5 (Applying, Analyzing and Evaluating). Connected to the result, the writer suggests teachers to practice teaching using this method to promote students’ higher order thinking skills as mentioned in k13 Curriculum.